Notes on the Stigmatophora palmata (Moore, 1878) species-group (Lepidoptera, Erebidae, Arctiinae, Lithosiini) from China with description of a new species - Xu, Yong-Qiang; Huang, Si-Yao; Volynkin, Anton V. (Zootaxa, 2025)
A peculiar new species of the Stigmatophora palmata (Moore, 1878) species-group, viz. S. nu Huang & Volynkin sp. nov. is described from Nujiang valley in extreme southeastern Xizang Autonomous Region and western Yunnan. The comparison is made with S. chekiangensis Daniel, 1951 and S. karenkonis (Matsumura, 1930). The distributions of S. hainanensis Fang, 1991 and S. danieli Volynkin, Huang & Dubatolov, 2021 are updated. The adults and genitalia of the aforementioned species are illustrated. An updated checklist of the S. palmata (Moore, 1878) species-group is provided.